(untitled) (INNOTEC, 2020)
Seasonal variations and interannual changes (2006-2019) of the phytoplankton community, related to variations in water quality and river discharge, in the lower part of the Uruguay River in South America are presented. In total, 422 microalgae and cyanobacterial taxa were identified. Cryptophytes, cyanobacteria, and diatoms were the most important groups. Although nanoflagellates and cryptophytes were always present in plankton, statistical differences were found in seasonal assemblages of phytoplankton. According to the similarity analysis (SIMPER), the typical species for each season were identified: Aulacoseira spp. in winter, Dolichospermum uruguayense, Durinskia baltica and Ankistrodesmus arcuatus in spring, Microcystis aeruginosa, M. wesenbergii, Dolichospermum uruguayense and D. circinale in summer and Ceratium cf. furcoides, A. arcuatus, Raphidiopsis and Jaaginema sp. in autumn. Under lentic river conditions (<2000 m3 s-1) and above 22ºC, high biomass was recorded due to the blooms of Microcystis and Dolichospermum. In 2010, M. panniformis reached 10.4 µg l-1 microcystin-LR. Raphidiopsis mediterranea and R. raciborskii began to be registered in Spring (2009 and 2014 respectively) reaching 1041 cell ml-1 in Spring 2017. This paper shows that flow, transparency and temperature are the main factors that regulate phytoplankton biomass and cyanobacterial blooms in the Uruguay River. In the summer, when the Uruguay River is in low flow conditions, cyanobacteria remain in the river. When flow increases, cyanobacteria are transported downstream and could reach the estuary of the Rio de la Plata, impacting its beaches.